The paranormal health beliefs scale: an evaluation using cognitive interviewing - Denovan, Andrew; Dagnall, Neil; Drinkwater, Kenneth Graham (Frontiers in Psychology, 2024)
Paranormal health beliefs denote the inclination to endorse illusory supernatural notions about well-being and treatment. These ideations are important since they potentially influence perceptions of health and allied behaviours. Noting this, researchers in Italy developed and verified the Paranormal Health Beliefs Scale (PHBS). Despite initial promising outcomes, the construct and measurement properties of the PHBS have remained under investigated. This is likely due to the fact that the instrument draws heavily on traditional Italian social, political, and religious influences and is overly culturally specific. Hence, items do not generalise well across populations and nationalities. Acknowledging these factors, this study used cognitive interviewing (think aloud protocol and concurrent probing) to assess the suitability of the PHBS for general use. Concurrently, the intention was to identify necessary modifications that would enhance scale performance. Fourteen interviewees (eight males and six females), evenly distributed across two rounds, participated. Round 1 focused on comprehension and perception of the PHBS. Cognitive interviews identified issues with culturally particular content/points of reference, phraseology, and wording. To address these a modified version of the PHBS was produced. Round 2 then examined the effectiveness of changes. Analysis revealed fewer concerns, although difficulties with ambiguity, complex terminology, and response scale appropriateness persisted. Overall, interviews indicated that a focus on illusory (rather than paranormal) health beliefs would improve scale utility. Methodologically, cognitive interviewing provided invaluable insights into the effectiveness of the PHBS and identified ways in which researchers could adapt the instrument for use with other cultures.